Mendelian randomization of stroke risk after total hip and knee replacements - Pang, Liang; Zheng, Zhihui; Su, Pingping; Xu, Zhouhengte; Chen, Yirui; Liao, Zhicheng; Jia, Pengcheng; Zhang, Xiuling; Lv, Cunxian (Frontiers in Genetics, 2024)
Objective: Previous epidemiological studies have indicated an increased risk of neurovascular diseases in patients following total hip and knee replacements. However, definitive conclusions regarding the increased risk of stroke post-replacement remain elusive. Therefore, we conducted a two-sample Mendelian randomization study to investigate the causal relationship between total hip and knee replacements and stroke.Methods: We utilized summary data from publicly available genome-wide association studies (GWAS). Data concerning total hip replacements (THR, N=319,037) and total knee replacements (TKR, N=252,041) were sourced from the Genetics of Osteoarthritis (GO) Consortium. Stroke-related data were obtained from the International Stroke Genetics Consortium, encompassing any stroke (AS), any ischemic stroke (AIS), large vessel ischemic stroke (LV-IS), cardioembolic ischemic stroke (CE-IS), and small vessel ischemic stroke (SV-IS). Our primary causal inference method was the inverse variance weighted (IVW) approach, supplemented by weighted median and MR-Egger regression as secondary inference methods. We utilized the MR-PRESSO global test for outlier detection, Cochran's Q statistic to assess heterogeneity, and assessed the multiplicity and stability of our findings using P-values from MR-PRESSO and MR-Egger regressions, and the leave-one-out method, respectively.We identified significant genetic associations between THR and both AS (IVW P=0.0001, OR=1.08, 95% CI=1.04-1.12) and AIS (IVW P=0.0016, OR=1.07, 95% CI=1.03-1.12). Significant associations were also observed between TKR and AS (IVW P=0.0002, OR=1.08, 95% CI=1.04-1.12), as well as AIS (IVW P=0.0005, OR=1.15, 95% CI=1.06-1.24).Our findings genetically support an increased risk of stroke following total hip and knee replacements. However, further studies are necessary to elucidate the specific mechanisms underlying stroke episodes post-replacement.